Strategies for primary and secondary stroke prevention - Brass, Lawrence M. (Clin Cardiol, 2009)
Of the 55 million deaths that occur annually, 1 in 10 is attributable to stroke. As a consequence, cerebrovascular disease is the second leading cause of death worldwide, and stroke is among the most devastating consequences of vascular disease, causing long‐term disability and incurring high personal, societal, and financial costs. However, stroke is a highly preventable disease in the majority of patients. The goal of stroke prevention strategies is to identify high‐risk patients through the presence of modifiable and nonmodifiable risk factors and to target these modifiable risk factors through the use of appropriate pharmacologic and nonpharmacologic interventions. Clinical and epidemiologic studies point toward three major risk‐reducing pharmacologic therapies that together may dramatically reduce stroke risk. First, landmark clinical trials have demonstrated that the reduction of blood pressure in persons at risk for cerebrovascular disease significantly reduces stroke risk. Second, ample evidence supports the use of antiplatelet therapy, such as aspirin, in patients at high risk for a cerebrovascular event. Third, an abundance of data suggests that lipid‐lowering therapy with a statin reduces stroke risk in most moderate‐ to high‐risk patients regardless of baseline cholesterol levels. Together, these data suggest that intensive therapy with agents from multiple drug classes that target two or more risk factors for cerebrovascular disease may provide additive—or even synergistic—reductions in stroke risk.